FLOUTING AND VIOLATION OF GRICEAN MAXIMS TO CREATE HUMOR BY AN INDONESIAN COMEDIAN “FAJAR SADBOY” - Sabrina, Adani Nur (Asosiasi Dosen Muda Indonesia, 2023)
This research discusses how flouting and violating the Gricean maxims of conversation can create humor, especially the ones that are done by an Indonesian comedian named Fajar Sadboy. The data are taken from a video on Raditya Dika’s YouTube channel with the title Bisakah Fajar Sadboy jadi Happyboy? By conducting this study, the researcher aims to find the maxims of conversation flouted and violated by Fajar Sadboy to create humor, as well as to analyze those floutings and violations. This is descriptive qualitative research with purposive sampling as the technique for gathering the data. The results show there are 15 data found which consist of 7 data of flouting and 8 data of violation; 6 data of maxim of quantity, 1 data of maxim of quality, 3 data of maxim of relation, 4 data of maxim of manner, and 1 data of the combination of maxims of manner and relation.